Conformational Cooling Dynamics in Matrix-Isolated 1,3-Butanediol - Rosado, Mário T. S. (2009)
The complete conformational space of monomeric 1,3-butanediol has been characterized theoretically, and 73 unique stable conformers were found at the MP2/6-311++G(d,p) level. These were classified into nine families whose members share the same heavy atom backbone configurations and differ in the hydrogen atom orientations. The first and third most populated backbone families are governed by the formation of an intramolecular hydrogen bond; however, the second precludes this type of interaction and was frequently overlooked in previous studies. Its stability is determined by the relatively high entropy of its main conformers. The hydrogen bonding of four of the most important conformers was characterized by means of atoms in molecules (AIM, also known as QTAIM) and natural bond orbital (NBO) analyses. Using appropriate isodesmic reactions, hydrogen bonding energy stabilizations of 12−14 kJ mol−1 have been found. Experimentally, monomeric molecules of 1,3-butanediol were isolated in low-temperature inert matrixes, and their infrared spectra were analyzed from the viewpoint of the conformational distribution. All the relevant transition states for the conformational interconversion reaction paths were characterized at the same level of theory to interpret the conformational cooling dynamics observed in the low-temperature matrixes. The energy barriers for rotation of the OH groups were calculated to be very low (<3 kJ mol−1). These barriers were overcome in the experiments at 10 K (Ar matrix), in the process of matrix deposition, and population within each family was reduced to the most stable conformers. Further increase in the substrate temperature (up to 40 K, Xe matrix) resulted in conformational cooling where the medium-height barriers (13 kJ mol−1) could be surmounted and all conformational population converted to the ground conformational state. Remarkably, this state turned to consist of two forms of the most stable hydrogen bonded family, which were predicted by calculations to be accidentally degenerated and were found in the annealed matrix in equal amounts. All of these experimentally observed conformational cooling processes were analyzed and supported by full agreement with the theoretical calculations.